COMMUNICATIVE PRAGMATICS OF PUBLICISTIC TEXTS: TRANSLATION ASPECT - Pavlyk, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article, the problems of text stylistics and translation studies are considered. In the research, the communicative and pragmatic factors of newspaper publicistic texts are determined and analyzed. Extralingual factors of creating the texts of publicistic texts are an important element of pre-translation text analysis. Modern science of translation considers two main fields: the research of rendering as the process of translation activity and as the result of this activity. The investigation of translation as a process is focused on the preparatory stage of high-quality translation execution, a pre-translation analysis of the text, i.e. the analysis of its communicative and pragmatic component. Text pragmatics is a complex of lingual and extralingual factors that provide with the implementation of text pragmatics through the influence on the addressee with both addresser’s intent and language form. The actants of text pragmatics are an addresser and an addressee. The addresser is embodied in the text as its creator, their points of view, taste or other qualities and, first of all, their specific aim of communication that in any case are implemented directly. The addressee implicitly dictates a text structure, a selection of lexical means and some other parameters of the text. The foremost extralingual factors that influence the specifics of publicistic texts are the sphere of activity within which the texts and communicative situation of genres are created and the components of which are accurately fixed in relation to each individual text. The components of communication situation are: a topic of communication, a subject of communication, an addresser, an addressee, additional conditions of communication. Functionally-communicative features of publicistic texts are invariant indications of speech genre which are based on its extralingual components and act as mediators between extralingual factors of the text and their language objectification. Composition and speech forms of publicistics texts are functional text and speech unities that structure the thought, put in order its development and give it wholeness and completeness. Acting as the law of language units organization, they are complicated syntactic complexes that are determined by the types of internal textual connection. The architectonic and speech forms that are monologue, dialogue, polylogue serve as the forms of implementation of the communicative and speech act. The tonality of publicistics texts encapsulate the concentration of all expressive means of the text that are applied by the author in their speech activity aiming at presentation of the essence of the subject matter and their own, personal attitude to it. The involvement of text communicative pragmatics to the process of translation and, as a result, the carried out pre-translation analysis of the text serves as the justification of effectiveness and adequacy of text translation.